Slack - Simon, Phil (--For dummies., 2020)
Explains how to use Slack to communicate and collaborate with colleagues, exploring the Slack user interface and its key features, covering such topics as how to provide additional context to group and individual messages, extend the power of Slack with third-party apps and integrations, and create workspaces, channels, and threads.